2014
DOI: 10.1186/s40199-014-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of the semi-purified fractions from the soft coral Eunicella singularis and isolation of pure compounds

Abstract: BackgroundGorgonians of the genus Eunicella are known for possessing a wide range of pharmacological activities such as antiproliferative and antibacterial effect. The aim of this study was to evaluate the anti-inflammatory and gastroprotective effect of the organic extract and its semi-purified fractions from the white gorgonian Eunicella singularis and the isolation and identification of pure compound(s) from the more effective fraction.MethodsAnti-inflammatory activity was evaluated, using the carrageenan-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Crude extract was fractionated into three semi-purified fractions were purified from F-EtOH fraction as described previously [22,23]. using InCyte ® software package.…”
Section: Purification and Isolation Of Natural Compoundsmentioning
confidence: 99%
“…Crude extract was fractionated into three semi-purified fractions were purified from F-EtOH fraction as described previously [22,23]. using InCyte ® software package.…”
Section: Purification and Isolation Of Natural Compoundsmentioning
confidence: 99%
“…The organic extracts of the coral were prepared by maceration and were examined for the presence of several class of compounds, i.e., polyphenols, alkaloids, saponins, steroids, terpenoids, and glycosides by qualitative chemical From 2013 to 2017, Deghrigue's group and Ioannou's group conducted thorough studies on E. singularis and Eunicella cavolini comprising preliminary biological evaluation of the organic extracts and fractions. It was found that the polar fractions show anti-inflammatory and analgesic potentials, as well as anti-proliferative effects on breast cancer cells MCF-7 and prostate cancer cells LNCaP, indicating the presence of novel bioactive compounds [19,[29][30][31][32]. The organic extracts of the coral were prepared by maceration and were examined for the presence of several class of compounds, i.e., polyphenols, alkaloids, saponins, steroids, terpenoids, and glycosides by qualitative chemical screening tests based on visible chemical change [29,31].…”
Section: Structural Diversity Of Terpenoids From Eunicella Spmentioning
confidence: 99%
“…The organic extracts of the coral were prepared by maceration and were examined for the presence of several class of compounds, i.e., polyphenols, alkaloids, saponins, steroids, terpenoids, and glycosides by qualitative chemical screening tests based on visible chemical change [29,31]. Final purification of fractions resulted in isolation of 2 terpenoids, palmonines D (5) and F (7), and nine steroids of various chemical structures (Section 2.3., vide infra) [30,32]. Moreover, Rosa et al first isolated diterpenoid 8 bearing two acetoxyl groups, from the E. cavolini acetone extract ( Figure 5) [21].…”
Section: Structural Diversity Of Terpenoids From Eunicella Spmentioning
confidence: 99%
“…Oral administration of the damaging agent to the control group clearly produced a mucosal damage characterized by multiple haemorrhage red bands of different sizes along the long axis of the glandular stomach [9].…”
Section: Gastroprotective Activitymentioning
confidence: 99%
“…After 30 min, gastric damage was induced in the experimental groups by 150 mM HCl/EtOH (40:60, v/v) orally administration (1 mL/100 g), while the control group received vehicle and the reference group received ranitidine (60 mg/ kg, i.p). One hour later, the animals were sacrificed and their stomachs rapidly removed and opened via an incision along the greater curvature [9]. Gastric damage was determined by measuring the extent of the ulcerative lesions.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%